2022
DOI: 10.1029/2021jb023832
|View full text |Cite
|
Sign up to set email alerts
|

Broad Elastic Softening of (Mg,Fe)O Ferropericlase Across the Iron Spin Crossover and a Mixed‐Spin Lower Mantle

Abstract: Introduction(Mg,Fe)O ferropericlase is the second most abundant mineral in Earth's lower mantle (e.g., Irifune et al., 2015). At room pressure, ferrous iron (Fe 2+ ) in ferropericlase adopts the high-spin electronic configuration where the six 3d-electrons partially fill the t 2g and e g orbitals, maximizing the number of unpaired electrons. At a pressure of about 40 GPa, a distortion of the iron-containing octahedral sites in the crystal structure triggers a change in iron electronic configuration to the low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 70 publications
(148 reference statements)
5
22
0
Order By: Relevance
“…Further studies have proposed alternative methods, which include a non-ideal mixing model, with and without the contribution of magnetic entropy (Sun et al, 2022). Building on this, we recently showed that good agreement is obtained with ambient-temperature experimental results if, rather than assuming ideal mixing of high-and low-spin states, one calculates the series of successive spin transitions between stable spin states, from high-to low-spin (Méndez et al, 2022). In this method Equation 1 is applied to each individual spin transition, ∆𝐺 𝐻𝑆−𝐿𝑆 (𝑃, 𝑇) is the difference between the static and vibrational components of the Gibbs free energy of the higher and lower spin states, XFe the fraction of iron weighted by the fraction of iron involved in the spin transition, and kB is the Boltzmann constant.…”
Section: Approach To Spin Transition Calculationsmentioning
confidence: 75%
See 4 more Smart Citations
“…Further studies have proposed alternative methods, which include a non-ideal mixing model, with and without the contribution of magnetic entropy (Sun et al, 2022). Building on this, we recently showed that good agreement is obtained with ambient-temperature experimental results if, rather than assuming ideal mixing of high-and low-spin states, one calculates the series of successive spin transitions between stable spin states, from high-to low-spin (Méndez et al, 2022). In this method Equation 1 is applied to each individual spin transition, ∆𝐺 𝐻𝑆−𝐿𝑆 (𝑃, 𝑇) is the difference between the static and vibrational components of the Gibbs free energy of the higher and lower spin states, XFe the fraction of iron weighted by the fraction of iron involved in the spin transition, and kB is the Boltzmann constant.…”
Section: Approach To Spin Transition Calculationsmentioning
confidence: 75%
“…In order to describe the correlated d electrons of iron in ferropericlase, we utilized the LDA+U scheme of Dudarev et al (1998), in which only the difference between onsite Coulomb interaction parameter U and onsite exchange parameter J is meaningful. In the present work, we used U -J = 3.3 eV, which was found to lead to the best agreement with experimental values for the spin crossover pressure in ferropericlase at 300 K (Méndez et al, 2022), and is similar to the 3.0 eV used in other studies of the spin crossover (Muir & Brodholt, 2015). Since the LDA is known to underestimate pressure, we calculated a correction using the method outlined by Oganov et al (2001), including the thermal pressure term calculated from our lattice dynamics calculations.…”
Section: Ab-initio Calculationsmentioning
confidence: 80%
See 3 more Smart Citations